Considering Maus : approaches to Art Spiegelman's "Survivor's tale" of the Holocaust - Geis, Deborah R. 1960- Hrsg (Univ. of Alabama Press, 2003)
Underground comics and survival tales : Maus in context / David Mikics -- The orphaned voice in art Spiegelman's Maus / Hamida Bosmajian -- Cartoons of the self : portrait of the artist as a young murderer--Art Spiegelman's Maus / Nancy K. Miller -- Necessary stains : Art Spiegelman's Maus and the bleeding of history / Michael G. Levine -- "Happy, happy ever after" : story and history in Art Spiegelman's Maus / Arlene Fish Wilner -- The language of survival : English as metaphor in Art Spiegelman's Maus / Alan C. Rosen -- "We were talking Jewish" : Art Spiegelman's Maus as "Holocaust" production / Michael P. Rothberg -- Read only memory : Maus and its marginalia on CD-ROM / John C. Anderson and Bradley Katz